Functional Characterization of Dense Granule Proteins in Toxoplasma gondii RH Strain Using CRISPR-Cas9 System - Bai, Meng-Jie; Wang, Jin-Lei; Elsheikha, Hany M.; Liang, Qin-Li; Chen, Kai; Nie, Lan-Bi; Zhu, Xing-Quan (Frontiers in Cellular and Infection Microbiology, 2018)
Infection with the apicomplexan protozoan parasite Toxoplasma gondii is an ongoing public health problem. The parasite’s ability to invade and replicate within the host cell is dependent on many effectors, such as dense granule proteins (GRAs) released from the specialized organelle dense granules, into host cells. GRAs have emerged as important determinants of T. gondii pathogenesis. However, the functions of some GRAs remain undefined. In this study, we used CRISPR-Cas9 technique to disrupt 17 GRA genes (GRA11, GRA12 bis, GRA13, GRA14, GRA20, GRA21, GRA28-31, GRA33-38 and GRA40) in the virulent T. gondii RH strain. The CRISPR-Cas9 constructs abolished the expression of the 17 GRA genes. Functional characterization of single ΔGRA mutants was achieved in vitro using cell-based plaque assay and egress assay, and in vivo in BALB/c mice. Targeted deletion of these 17 GRA genes had no significant effect neither on the in vitro growth and egress of the mutant strains from the host cells nor on the parasite virulence in the mouse model of infection. Comparative analysis of the transcriptomics data of the 17 GRA genes suggest that GRAs may serve different functions in different genotypes and life cycle stages of the parasite. In sum, although these 17 GRAs might not be essential for RH strain growth in vitro or virulence in mice, they may have roles in other strains or parasite stages, which warrants further investigations.